Fungi from decaying wood samples of Hibiscus tiliaceous and lumnitzera racemosa in Taklong Island, Guimaras. - Guillermo, Syril Bren Paraton
Mangrove is considered as one of the most biologically productive areas on earth. Marine fungi are important component of this highly productive detritus based ecosystem . They have significant role in the breakdown of jitters, tree materials and other lignocellulosic materials. In this environment, fungi rather than bacteria are considered as the main decomposers. Presently, the occurrence of mangrove fungi has been intensely studied in tropical areas. However, despite these considerable knowledge of manglicolous fungi in intertidal habitat, little is known on the occurence on identified host species. There are few published data on the occurence of manglicolous fungi from Hibiscus tiliaceous but none on Lumnitzera racemosa., This study aims to gather valuable information on the mycota in Taklong Island specifically from woods of Hibiscus tiliaceous and Lumnitzera racemosa. This study is concerned on the identification of morphological features and classification of fungi associated to these plants. This particular study aims to (1) determine the occurence of fungi on decaying wood samples of Hibiscus tiliaceous and Lumnitzera racemosa and to (2)measure the biodiversity of fungi on Hibiscus tiliaceous and Lumnitzera racemosa. (p)Three collections (October 1997, July and November 1998) were made from selected sites along the U.P. channel, Taklong Island National Marine Reserve where Hibiscus tiliaceous and Lumnitzera racemosa are abundantly situated. The isolation of fungal species was done at the U.P.V. Biological Sciences laboratory in Miagao and the documentation such as photography was done in the Department of Agriculture laboratory in Leganes. Sixteen fungal species were isolated from the three hundred decaying stems of Hibiscus tiliaceous and Lumnitzera racemosa. Twelve species belong to Ascomycota, three species belong to Deuteromycota and one species belong to Basidiomycota. Eleven from sixteen fungal species were present on Hibiscus tileaceous and nine fungal species were isolated from Lumnitzera racemosa. The isolated species include Frondicola sp., Leptosphaeria sp., Cryptovalsa halosarceicola, Fusarium oxysporum, Didymosphaeria sp., Marinosphaeria sp., Kallichroma tethys, Tetracoccosporium paxianum, Penecillium sp., Swampomyces sp. and six unidentified species. These were Ascomycete 1, Ascomycete 2, Ascomycete 3, Ascomycete 4, Deuteromycete 1 and Basiodiomycete 1. Factors such as nature of the substrata and specificity on the host may have influenced the presence of fungi on these hosts.